Between Headlines and Hallways: The Cost of Ideological Policy on 2SLGBTQIA+ Youth - Bussière-Prytula, Michelle; Schenk, Adrienne; Florizone, Christopher (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2026)
The purpose of this study was to explore the impacts of anti-2SLGBTQIA+ sentiments in mainstream media on 2SLGBTQIA+ youth. Using the Minority Stress Framework and a case study format, qualitative interviews were conducted with 15 youth. While participants described the impact of media-driven stigma and negativity, many directly referenced Saskatchewan’s “pronoun policy,” viewing it as an institutional reinforcement of anti-2SLGBTQIA+ sentiment. The policy made discrimination feel targeted, immediate, and personal for these participants. Discussions of social exclusion, safety concerns, and institutionalized discrimination reflect the harmful influence of restrictive governance policies. These findings build on existing research on the compounding impacts of minority stress and institutional stigma in education and underscore the need for responsible and inclusive education policy and governance.